algebra 1

posted by .

1. Solve the linear system using substitution.

4x-y=5
4x+4y=-4

• algebra 1 -

substitute y=4x-5 into 4x+4y=-4 to get

4x+4(4x-5) = -4
4x+16x-20 = -4
20x = 16
x = 4/5
so, y = -9/5

Similar Questions

1. Algebra - solving linear equations w/ substitution

The question in the book reads: "Suppose you try to solve a system of linear equations using substitution and get this result. How many solutions does each system have?
2. Algebra 2

2 questions: 1. Find "a" if (=3,7) is a solution of 2x+ay=26 2. solve system using substitution, linear combination, and graphing: 3x-2y=3 5x+4y=16
3. maths

use the substitution method to solve the linear system. 1. 3x=9 -x+2y=9 3x/3 = 9/3 x = 3 -x(3)+2y = 9 -3+2y = 9 2y = 12 y = 6 is (3,6) correct?
4. Algebra

solve the linear system using substitution 4x - y=5 4x + 4y= -4 Also by using elimination.
5. Algebra 1

Okay. So I am completely lost with this... Any help would be great! 3. Solve the system using any method – graphing, substitution, or linear combination. Make sure to show your work. 2x + 5y= 8 x + 3y= 2
6. Algebra

I have a few questions I need help with! 1. Solve the system by triangularizing the augmented matrix and using back substitution. If the system is linearly dependent, give the solution in terms of a parameter. -3x+y-z=-4 6x-2y+2z=8 …
7. Algebra help!

1.) Solve the system by triangularizing the augmented matrix and using back substitution. -x-y+z=1 x-y-4z=-7 4x+y+z=6 2.) Perform the indicated row operation, then write the new matrix. -4 4 | 4 9 -6 | 5 -2R1+ R2 ---> R2 3.) Solve …
8. Algebra

Solve the system of linear equations using the substitution method. 3x + 3y = 0 -6x + 9y = -10
9. Algebra

Solve this system of linear equations. * Used the substitution method 3x - y = 8 4x - y = -15 ----------------------------------------- WORK y = 3x - 8 4x - (3x - 8 ) = -15 4x - 3x + 8 = -15 x + 8 = -15 x = -7 3x - y = 8 3(-7) - y …
10. Math

17) solve this linear system using the method of substitution. 2y-x=-10 y= -3/2x-1 20) simplify then solve by substitution 2(x-4)+y=6 3x-2(y-3)=13 just need help with these 2.

More Similar Questions